Demokrasi di Malaysia: Studi Perbandingan Periode Pemerintahan Tiga Perdana Menteri Malaysia - Mohammad Fauzi (Universitas Muhammadiyah Yogyakarta, 2015)
This study aimed to compare the historical descriptive-interpretative effect general election implementation and socio-economic and cultural conditions of democracy and democratic process in Malaysia during the government period of Tunku Abdul Rahman to Mahathir Mohamad. The research based on the secondary data study-method. Based on the research, the general election implementation and socio-economic and cultural condition do not significant effect on democracy and the democratic process in Malaysia, except in the middle of Tun Abdul Razak’s government which the socio-economic conditions have a significant effect on democracy in Malaysia.